The role of purchasers and payers in the clinical research enterprise : workshop summary - Tunis, Sean; Korn, Allan; Ommaya, Alex (National Academy Press, 2002)
"The goal of the workshop that is the topic of this summary report ... was to examine how purchasers and payers interact with the various components of the clinical research enterprise and to understand their perspective on what the vision of the enterprise should be."